2000
DOI: 10.1007/bf02988217
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and marked breast uptake of both123I-BMIPP and99mTc-TF by myocardial scintigraphy

Abstract: Unexpected breast uptake was observed in a 32-year-old woman referred for evaluation of hypertrophic cardiomyopathy. Diffuse and marked bilateral breast uptake of 123I-BMIPP and 99mTc-TF was shown by both planar and SPECT imaging during the first study, and the uptake of both radionuclides had decreased significantly eleven months later. At the time of the first radionuclide examination, she was occasionally breast feeding her 2-year-old child and had small amounts of milk production. At the follow up examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Bilateral breast uptake of 99m Tc-MIBI during the menstrual cycle and in the postmenopausal course has been reported, with 58% and 72% of the cases in the first and fourth weeks of the menstrual cycle, respectively, and with 5% of postmenopausal women studied [11]. Our patient was in the fourth week of her menstrual cycle.…”
mentioning
confidence: 56%
“…Bilateral breast uptake of 99m Tc-MIBI during the menstrual cycle and in the postmenopausal course has been reported, with 58% and 72% of the cases in the first and fourth weeks of the menstrual cycle, respectively, and with 5% of postmenopausal women studied [11]. Our patient was in the fourth week of her menstrual cycle.…”
mentioning
confidence: 56%
“…Focal breast uptake of 99m Tc-MIBI, 201 Tl-, and 99m Tc-tetrofosmin has been serendipitously reported in malignant breast masses 3,4 a finding that led to use of these tracers for scintimammography to improve diagnostic accuracy 5,6 . However, diffuse bilateral breast uptake of 99m Tc-MIBI has only been reported in anecdotal case reports of postpartum patients 7,8 . Stabin et al 9 have shown that only 0.03% of initial 99m Tc dose is excreted in the breast milk.…”
mentioning
confidence: 99%
“…5,6 However, diffuse bilateral breast uptake of 99m Tc-MIBI has only been reported in anecdotal case reports of postpartum patients. 7,8 Stabin et al 9 have shown that only 0.03% of initial 99m Tc dose is excreted in the breast milk. Even in a hypothetical scenario of continued breast feeding, an infant would receive a dose of 0.52 rem/mCi.…”
mentioning
confidence: 99%